Enhancing ultrafiltration performance by gravity-driven up-flow slow biofilter pre-treatment to remove natural organic matters and biopolymer foulants. (1st May 2021) - Xu, Lei; Zhou, Zheng; Graham, Nigel J.D.; Liu, Mengjie; Yu, Wenzheng
Highlights: Bench-scale GUSB is trialed as the pre-treatment for UF process first time. GUSB can significantly reduce NOM and biopolymers in natural water. HRT is a key factor influencing the performance of GUSB. Pre-treatment via GUSB shifts the microbial diversity on membrane surface. Biopolymers determine the structure of biofilm and therefore the fouling rate. Abstract: Membrane fouling by influent biopolymers, and the formation of surface biofilms, are major obstacles to the practical application of membrane technologies. Identifying reliable and sustainable pre-treatment methods for membrane filtration remains a considerable challenge and is the subject of continuing research study worldwide. Herein, the performance of a bench-scale gravity-driven up-flow slow biofilter (GUSB) as the pre-treatment for ultrafiltration to reduce membrane fouling is presented. Dissolved organic carbon (DOC) was shown efficiently removed by the GUSB (around 80%) when treating a natural water influent. More significantly, biopolymers, with molecular weight (MW) between 20 kDa and 100 kDa, were effectively removed (62.8% reduction) and this led to a lower rate of transmembrane pressure (TMP) development by the UF membrane. Microbial diversity analysis further unraveled the function of GUSB in shaping microbes to degrade biopolymers, contributing to lower accumulation and different distribution pattern of SMP on the membrane surface. Moreover, the biofilm formed on the membrane surface after the pre-treatment of GUSB was observed to have a relative porous structure compared to the control system, which can also affect the fouling development. Long-term operation of GUSB further revealed its robust performance in reducing both natural organic matters and UF fouling propensity. This study overall has demonstrated the potential advantages of applying a GUSB to enhance UF process performance by reducing biofouling and improving effluent quality. Graphical abstract: Image, graphical abstract